Carbonation characteristics of cement-based materials under the uniform distribution of pore water. (15th March 2021) - Yahui, Yang; Gang, Xu; Bin, Tian
Graphical abstract: Highlights: A study of the impact of pre-treatment methods on cement-based materials carbonation. A proposed pre-treatment method for the uniform distribution of pore water. There is a correlation between carbonation characteristics of cement-based materials and relative humidity. Consistency in laboratory accelerated carbonation with that in natural environment. Abstract: Two different moisture pre-treatment methods were used for the mortar specimens, and the carbonation tests were performed simultaneously. Results show that moisture transmission had a significant impact on the depth and degree of carbonation. A new pre-treatment method was proposed for the uniform distribution of the mortar specimens in the pore water. Furthermore, the carbonation characteristics of cement-based materials in uniformly distributed pore water under different ambient relative humidity were studied. The accelerated carbonation test using the uniformly distributed pore water was more consistent with the natural carbonation law.